The Feasibility, Acceptability, and Efficacy of Cognitive Resilience Training among College Students with Mental Health Symptoms: A Parallel Group-Randomized Trial Protocol - Rotimi, Oguantayo; Portillo Reyes, Veronica; Ochoa Meza, Gerardo; Gutierrez Vega, Marisela (2024)
Psychological Distress Comorbid with Suicidal Episodes (PDCSE) is one of the most common occurrences among college students. Protocols could guide the treatment of such disorders. Therefore, this study developed and provided parameters for assessing the effectiveness, acceptability, and feasibility of Cognitive Resilience Training (CRT) using a parallel Group Randomized Trial (GRT) among students with symptoms of anxiety, depression, and suicidal ideation. This protocol study adopted a one-year, single-blind, parallel group-randomized trial (GRT). A total of 60 students were enrolled using randomized block calculations in the Servicios de Atención Psicológica Universitario (SUAPSI) of the Universidad Autónoma de Ciudad Juárez (UACJ), Juárez, Mexico. Data will be collected using a questionnaire pack comprising the general anxiety disorder-2, patient health questionnaire-2, Plutchik suicide risk scale, brief resilience scale, competence scale for psychoeducation, and psychotherapy-specific treatment satisfaction scales. The expected results of this study are that participants will improve in cognitive resilience skills while reducing PDCSE. Additionally, CRT feasibility and acceptability will be ascertained using indicators such as client satisfaction scores, attendance, retention, and dropout rates of participants. This study has determined the pathway to confirm the feasibility, acceptability, and effectiveness of a cognitive resilience intervention among college students with psychological distress comorbid with suicidal episodes